FLIPPED CLASSROOM AND ITS USE IN TEACHING ENGLISH AS A FOREIGN LANGUAGE - Soliyeva Ruxshona Davlatjon qizi; Axmedov Hasan Uzairovich (TADQIQOTLAR.UZ, 2024)
The usefulness of the flipped classroom teaching method in an English language classroom setting is investigated in this study. The study focuses on how students are developing their foreign language communication skills, what participants thought of the flipped classroom, and how to find solutions for the problem of poor assignment completion. The author's experiment at the University of Granada (Spain) with a group of undergraduate students enrolled in a required foreign language course provided the basis for the statistics that are being presented.